Moral Disengagement Pada Remaja Pengguna Media Sosial “Sebuah gagasan konseptual untuk konselor” - As’ad; Moh. Hafid (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
This article conceptually discusses the moral disengagement that occurs in adolescents on social media. Moral form is manifested as the power to refrain from inhumane behavior and the proactive power to behave humanely. The self-regulatory mechanisms that regulate moral behavior are activated by many psychosocial maneuvers in which moral sanctions selectively determine which behavior is human or inhuman. Moral disengagement can be interpreted as restructuring inhumane behavior to become as if it were appropriate with various reasons of justification. Moral disengagement on social media has reached a phenomenon that reduces human values, especially with the number of photos and videos that are diffusion of responsibility, such as flexing or sexuality. Counselors who assist adolescents in completing their developmental tasks need to provide guidance as a responsibility to minimize the effects of dehumanizing nature.